APPLICATION OF THE NEW METHOD TO DETERMINE THE MAIN STRUCTURE OF THE PRE-CENOZOIC BASEMENT IN THE GULF OF TONKIN AND ADJACENT AREA - Dung, Nguyen Kim (Vietnam Journal of Marine Science and Technology, 2016)
In this paper, the author applies the method of Oruç, B., et al., (2013), which uses the curvature gravity gradient tensor, in combination with the field transform method to outline the main structural partitions of the Pre-Cenozoic basement rock in the Gulf of Tonkin and adjacent are. The method was tested on the digital model and applied to factual data. The applied method gave the qualitative results quickly and fairly accurately. The contour 0 of big eigenvalue  delineated the spatial location of the edges of the anomalous sources with positive residual density, the contour 0 of small eigenvalue  delineated the spatial location of the edges of the anomalous sources with negative residual density. The locus of the contours 0 of the product of the eigenvalues  at the upward continuation levels of the potential field expressed fluctuations on the main structure at the different depths. The positive values represented the anticline, for example Thanh Nghe anticline, Ha Long anticline … The negative values expressed the syncline quite clearly, for example Dong Quan syncline, Quang Ngai syncline ... The qualitative results are relatively consistent with some research results which have been previously published.